2011
DOI: 10.3109/17482968.2011.593036
|View full text |Cite
|
Sign up to set email alerts
|

Progression of white matter degeneration in amyotrophic lateral sclerosis: A diffusion tensor imaging study

Abstract: Whether longitudinal diffusion tensor MRI imaging (DTI) can capture disease progression in patients with amyotrophic lateral sclerosis (ALS) is unclear. The primary goal of this study was to determine if DTI detects progression of the corticospinal tracts (CST) degeneration in ALS. Seventeen ALS patients and 19 age- and gender-matched healthy controls were scanned with DTI at baseline for cross-sectional analyses. For longitudinal analyses, the ALS patients had repeat DTI scans after eight months. Tractography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
41
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 36 publications
7
41
2
2
Order By: Relevance
“…Microstructural degeneration of the caudal WM tracts confirms previous DTI studies (van der Graaff, de Jong et al 2009, Prudlo, Bissbort et al 2012, Sheelakumari, Madhusoodanan et al 2015. Previous DTI studies using an ROI method showed a bilateral reduction in FA along the CST (Jacob, Finsterbusch et al 2003) while other studies found changes in CST to be confined to the right hemisphere (Zhang, Schuff et al 2011). The changes in motor pathways over time are consistent with the known atrophy in ALS (Jacob, Finsterbusch et al 2003, Keil, Prell et al 2012).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Microstructural degeneration of the caudal WM tracts confirms previous DTI studies (van der Graaff, de Jong et al 2009, Prudlo, Bissbort et al 2012, Sheelakumari, Madhusoodanan et al 2015. Previous DTI studies using an ROI method showed a bilateral reduction in FA along the CST (Jacob, Finsterbusch et al 2003) while other studies found changes in CST to be confined to the right hemisphere (Zhang, Schuff et al 2011). The changes in motor pathways over time are consistent with the known atrophy in ALS (Jacob, Finsterbusch et al 2003, Keil, Prell et al 2012).…”
Section: Discussionsupporting
confidence: 84%
“…There was reduced FA in the CC (Matsuo, Mizuno et al 2008, Avants, Cook et al 2010, Whitwell, Avula et al 2010, McMillan, Brun et al 2012) and more anteriorly when not corrected for multiple comparisons (Zhang, Schuff et al 2011). …”
Section: Commissural Fibersmentioning
confidence: 98%
See 1 more Smart Citation
“…Other DTI studies in ALS have reported apparent lateralization of CST involvement to the right upper CST. 13,40 There is also an under-recognized post mortem observation of potential relevance that the human CST is asymmetric in 75% of individuals, with 75% of these cases having a larger decussation to the right-sided cord CST. 41 However, FA changes have been observed in the PLIC on both affected and nonaffected sides according to disease burden, 32 and they appear bilaterally in DTI metaanalysis.…”
Section: Disease Duration and Apparent Lateralizationmentioning
confidence: 99%
“…8,9 Longitudinal studies in ALS have demonstrated a range of FA reductions over time. [10][11][12][13] In 2 cross-sectional studies, greater FA values were noted among those patients with the longest disease durations, 6,9 with the possibility that absolute FA values might have inherent prognostic value. In a survival analysis using whole CST FA measurement, lower values were a significantly adverse covariate.…”
mentioning
confidence: 99%